Optimization of transmission towers considering the bolt slippage effect. (15th May 2020) - de Souza, Rafael Rodrigues; Fadel Miguel, Leandro Fleck; Kaminski-Jr, João; Lopez, Rafael Holdorf; Torii, Andre Jacomel
Highlights: Nonlinear bolt slippage effect is included in the optimization through a two-stage based procedure. The optimization is applied to a real 230 kV TLT submitted to nine load cases and code constraints. The best result found achieves a 16% weight reduction when compared to the size optimization of the original design. It is possible to find towers with low weight that simultaneously present behavior close to linear. Constructional advantages and lower weight achieved, although its nonlinear behavior. Abstract: In a previous contribution (de Souza et al., 2016), the authors proposed a flexible approach for the optimization of self-supporting transmission line towers (TLT). The scheme takes into account constructional and structural features to allow a direct industrial application. For instance, according to CIGRÉ (2009), de Souza et al. (2019), the magnitude of the bolt slippage effect is highly dependent on the tower topology. Therefore, this optimization procedure allows limiting the topologies options aiming to minimize the bolt slippage behavior while maintaining a simple linear elastic analysis. In contrast with this approach, in the present study the connections' slippage is included in the mechanical model. Due to the computational cost required to solve the nonlinear problem, a two-stage optimization procedure is employed. Firstly, a linear elastic model is used to locate an optimum region and to provide a starting point to the next search. Then, the nonlinear bolt slippage is included to refine and improve the optimization. Through this procedure it is possible to search for broader topologies possibilities that can lead to lighter structures or attain configurations that present erection advantages. For the numerical example, a single circuit, self-supported 230 kV TLT subjected to nine different load cases is assessed. It is shown that the proposed scheme is able to furnish solutions with constructional advantages and reduce up to 14.6% of the structural weight, when compared to a classical size optimization procedure on original structures.